Development of a 3D Model of the STMIK TIME Campus Building Using the Photogrammetry Metho - Lie, Felix; Aryanto, Didik; Hoki, Leony (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2025)
Photogrammetry is a mapping method that utilizes photographic images to generate three-dimensional (3D) models. In this study, the photogrammetry method is used to create a 3D model of the STMIK TIME campus buildings to document and visualize the structures digitally. The process of creating the 3D model begins with image acquisition using a digital camera, followed by processing with photogrammetry software to generate point clouds, meshes, and textured models. The final result of this research is a 3D model of the STMIK TIME campus, which can be used for various purposes such as architectural planning, building preservation, and visual simulation. Based on the evaluation conducted, the resulting 3D model demonstrates a high level of accuracy in representing the actual building structure. Thus, the photogrammetry method has proven to be an effective technique for creating 3D building models at a more affordable cost compared to conventional 3D modeling techniques.